Social contexts in social work : a view from teachers in the centro east and colombian caribbean región (2024)
Objective: To reveal, from the point of view of the teachers dedicated to the training of social workers, the meanings they attribute to the social contexts in order to establish relationships with the training emphases proposed by the social work programs in the Caribbean and central-eastern regions of the Colombian territory. Theoretical Framework: oriented from the study group methodology, where the exchange of knowledge was the basis for analyzing and deciding the basic theoretical course for the configuration of historical and theoretical perspectives of the developed process, based on local sociologies to understand life contexts of subjects and communities, which paraphrasing Wiebke Keim (2010) work the dynamics of the local, recovering the voices of actors against the classical social theory that marked even the powers of the so-called North Atlantic. Method: the study was developed from the hermeneutic paradigm, qualitative approach, non-probabilistic designs, focus group technique and discourse analysis, aimed at teachers of Social Work Programs. Results and Discussion: the relationship of the context as a scenario where interactions are developed is reaffirmed, product of an economic structure that determines certain social representations, built in the groups permeated by social dynamics and intervention processes influenced by diagnoses that give reading to social, economic and political determinants that allow their development. Research Implications: It contributes to the epistemological, theoretical and methodological developments of Social Work from the reading of context. Originality/value: It provides views of context related to the emphasis of training that give sense to areas of professional performance.